Alteraciones electrocardiográficas como predictores de mortalidad intrhospitalaria en pacientes con enfermedad cerebrovascular aguda - Rivas Morán, Carlos Eudardo (2015)
To identify electrocardiographic alterations that are predictors of hospital mortality in patients with acute cerebrovascular disease (ECV) hospitalized in the Neurology´s Service of Trujillo Belén Hospital. Material and methods: Observational, analytical, retrospective case-control, performed in patients older than 65 years with acute ECV during the period of January 2008 to August 2012. Results: The electrocardiographic alterations associated with hospital mortality in patients with acute brain vascular disease were QTc prolongation (X2 = 38.96, p <0.01) and non-specific left ventricular repolarization abnormalities (X2 = 20.18, p <0.01). Logistic regression analysis of electrocardiographic changes with the event of death or survival, showed that non-specific ventricular repolarization abnormalities [OR: 61.0 (IC95% 15.0 – 247.9) p<0.01], prolongation of QTc interval [OR: 43.0 (IC95% 12.1 – 159.3) p<0.01], atrial fibrillation [OR: 24.7 (IC95% 6.0 – 97.7) p<0.01] and complete right bundle branch block [OR: 13.4 (2.6 – 68.6) p<0.01] are predictors of mortality. Conclusion: Non-specific left ventricular repolarization abnormalities, QTc prolongation, atrial fibrillation and complete right bundle branch block in patients with acute cerebrovascular disease are predictors of risk of death when it occurs within the first 48 hours of stroke